ANALISIS PENGARUH FAKTOR-FAKTOR FUNDAMENTAL DAN MEKANISME CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Elga Yulia Panggabean; Mathius Tandiontong (Jurnal Riset Akuntansi dan Bisnis, 2017)
This study is aimed to explain the relationship of fundamental factors(liquidity, profitability, leverage, share public, and size) and corporategovernance mechanism (commissioner board, independent commissioner board,Institutional ownership, and managerial ownership) to CSR disclosure inIndonesia. The sample in this study is Indonesian banking listed in 2011-2015whose annual reports disclose. CSR activities and can be accessed at IndonesianStock Exchange website. There are 28 samples applying purposive samplingtechnique. This study use analysis method regression linear. The results show thatthere is no significant relationship between liquidity, share public, profitabilityand CSRD. In contrast, positive significant relationship between leverage,independent commissioner board, commissioner board, institutional ownership,management ownership, size and CSRD are found.